Summary of American Journal of Evaluation, Volume 25(4), 2004 - Melvin M. Mark (The Evaluation Center at Western Michigan University, 2005)
The following is excerpted from the introduction to Volume 25, Issue 4 of the American Journal of Evaluation, by former AJE editor Dr. Melvin M. Mark. It is reprinted here with permission from Dr. Mark; AJE's current editor, Dr. Robin Miller; and the American Evaluation Association (AEA).The American Journal of Evaluation is the official journal of the American Evaluation Association and is distributed to AEA members as part of their membership package. To learn more about AEA and how to receive AJE, please go to www.eval.org.